2018
DOI: 10.1177/0272989x18792283
|View full text |Cite
|
Sign up to set email alerts
|

Nonidentifiability in Model Calibration and Implications for Medical Decision Making

Abstract: Background. Calibration is the process of estimating parameters of a mathematical model by matching model outputs to calibration targets. In the presence of nonidentifiability, multiple parameter sets solve the calibration problem, which may have important implications for decision making. We evaluate the implications of nonidentifiability on the optimal strategy and provide methods to check for nonidentifiability. Methods. We illustrate nonidentifiability by calibrating a three-state Markov model of cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 65 publications
0
41
0
Order By: Relevance
“…Generally, underidentifiability would be addressed through the inclusion of additional targets (if available), narrower prior distribution ranges (if these are known), or fewer parameters (e.g., less age stratification), not calibration itself. 42…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, underidentifiability would be addressed through the inclusion of additional targets (if available), narrower prior distribution ranges (if these are known), or fewer parameters (e.g., less age stratification), not calibration itself. 42…”
Section: Discussionmentioning
confidence: 99%
“…We found that the best-fitting parameter set from the initial random sampling stage was different each time we reran IMIS because of the low sampling density relative to the high dimensionality or the parameter space; 12 targets to inform 24 parameters yields underidentifiability and the possibility of many parameter sets fitting the targets equally well. 42…”
Section: Methodsmentioning
confidence: 99%
“…The reasons cited for nonidentifiability include an insufficient number (or type) of calibration targets, an excessive number of unknown model parameters, a large parameter space, or an inappropriate GOF criterion. 25 We have attempted to mitigate nonidentifiability in this work by presenting a multiobjective approach that eliminates the possibility of a single GOF criterion and a conservative parameter range Θ . In addition, we note that heuristics proposed to assess nonidentifiability, such as the collinearity index, are available.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we note that heuristics proposed to assess nonidentifiability, such as the collinearity index, are available. 25…”
Section: Discussionmentioning
confidence: 99%
“…Some parameters of the mathematical model, like the per-partnership transmission probability and the duration of natural immunity, cannot be informed directly by observed data, so we estimated the parameters by calibrating the transmission models (empirical and A-P) to age-specific pre-vaccination prevalence of HPV16 in Britain [29]. To account for potential non-identifiability, we adopted a Bayesian framework [30]. Briefly, we defined prior distributions on parameters of interest, then used incremental mixture importance sampling (IMIS) [31,32] to estimate posterior distributions of the parameters conditional on the prevalence data.…”
Section: Methodsmentioning
confidence: 99%